MO470: Outcomes of Patients in Advanced Chronic Kidney Disease (ACKD) Consultation With Covid-19 Infection. (3rd May 2022) - Carlos Herrero Berron, Juan; Suso, Andrea; Mon, Carmen; Ortiz, Milagros; Sanchez, Maria; Camacho, Rosa; Lentisco, Carolina; Oñate, Irene; Oliet, Aniana
Abstract: BACKGROUND AND AIMS: The coronavirus disease 2019 (COVID-19) has affected our patients not only in renal replacement therapy (RRT), but also in advanced chronic kidney disease (ACKD) consultation. Our aim is to assess the impact of COVID-19 in a group of patients of our ACKD consultation. METHOD: Retrospective observational study in our centre of patients from ACKD consultation with hospitalization due to COVID-19 infection in the period from March to December 2020. We have studied demographic parameters, characteristics during hospitalization, analytics values (3 months before and 1, 3, 6 and 12 months after infection) and final status at the end of follow-up on 31 December 2021. A value comparison is made with the Wilcoxon test for paired data. RESULTS: In an ACKD consultation with 90 patients, 12 (13%) required hospitalization due to COVID-19. 75% were male, with a mean age of 77.6 years (SD 7) (range 59–89 years) and 25% due to Diabetic Kidney Disease. Mean time in consultation 28 months (SD 14) (range 12–58). Mean Comorbidity Charlson Index 8.2 (SD 1.2) (range 7–11), all hypertensive, 42% treatment with insulin, 25% ischemic heart disease and 42% chronic obstructive pulmonary disease. In COVID-19 hospitalizations, 83% they had pneumonia, 50% steroid treatment, 75% hydroxychloroquine, 92% several antibiotics, 33% low molecular weight heparin, only two required tocilizumab, and none required admission to the intensive care unit. During hospitalization, 3 (25%) patients died, and one died during follow-up, all were males. The consequences after infection: 42% pneumology (cough, varying degrees of shortness of breath), 8% neurological (headaches, varying degrees of memory loss) and 8% loss of smell (from 1 to 6 moths). At the follow-up, only one patient needs RRT with haemodialysis (at 19 months after COVID-19). Table 1 shows analytics comparison before and after COVID. From 6 months after COVID, the results are like 3 months after the disease. CONCLUSION: With the important limitation of few patients and without a control group, ACKD patients with hospitalization to COVID-19 show similar patterns to those with RRT: more frequent in males, advanced age, lung comorbidity and diabetics, elevation of inflammatory parameters, anemia and increase in creatinine during hospitalization. Recovery to values prior to admission occurs from the first month after infection.